2016
DOI: 10.1007/s00167-016-4144-8
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate-retaining total knee arthroplasty: How much of the PCL is really retained?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Similar outcomes of CR-and PS implants for varus knees have been reported in terms of survivorship, range of movement, proprioception, and gait analysis and this is now well established. [18][19][20][21] However, the use of CR implants for valgus knees is less studied but gaining popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar outcomes of CR-and PS implants for varus knees have been reported in terms of survivorship, range of movement, proprioception, and gait analysis and this is now well established. [18][19][20][21] However, the use of CR implants for valgus knees is less studied but gaining popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue injury to the medial or lateral collateral ligament (MCL or LCL), posterior cruciate ligament (PCL), or extensor mechanism may compromise postoperative clinical outcomes, through reduced stability and decreased implant survivorship. 1-5 Studies have shown that a full transverse tibial cut may lead to damage to the PCL 6-8 and even to the deep MCL. 9 PCL avulsion has been shown to be more likely with increased sagittal slope.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk of the PCL is found in the distal part of PCL insertion [ 19 ]. Totlis et al studied tibial footprint of PCL in 30 female patients on MRI preoperatively and intraoperatively measured the length of footprint removed with the tibial cut [ 20 ]. They found that 65.1 ± 15.9 % of the footprint length may be lost in the tibial cut.…”
Section: Discussionmentioning
confidence: 99%